Functional Connectivity in the Pontomedullary Respiratory Network - Segers, Lauren S. (American Physiological Society, 2008)
Current models propose that a neuronal network in the ventrolateral medulla generates the basic respiratory rhythm and that this ventrolateral respiratory column (VRC) is profoundly influenced by the neurons of the pontine respiratory group (PRG). However, functional connectivity among PRG and VRC neurons is poorly understood. This study addressed four model-based hypotheses: 1) the respiratory modulation of PRG neuron populations reflects paucisynaptic actions of multiple VRC populations; 2) functional connections among PRG neurons shape and coordinate their respiratory-modulated activities; 3) the PRG acts on multiple VRC populations, contributing to phase-switching; and 4) neurons with no respiratory modulation located in close proximity to the VRC and PRG have widely distributed actions on respiratory-modulated cells. Two arrays of microelectrodes with individual depth adjustment were used to record sets of spike trains from a total of 145 PRG and 282 VRC neurons in 10 decerebrate, vagotomized, neuromuscularly blocked, ventilated cats. Data were evaluated for respiratory modulation with respect to efferent phrenic motoneuron activity and short-timescale correlations indicative of paucisynaptic functional connectivity using cross-correlation analysis and the “gravity” method. Correlogram features were found for 109 (3%) of the 3,218 pairs composed of a PRG and a VRC neuron, 126 (12%) of the 1,043 PRG–PRG pairs, and 319 (7%) of the 4,340 VRC–VRC neuron pairs evaluated. Correlation linkage maps generated for the data support our four motivating hypotheses and suggest network mechanisms for proposed modulatory functions of the PRG.